Frontiers in Protein Structure Research - Simon, Istvan; Magyar, Csaba (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue, we aim to represent the vibrant state of protein structure studies at the end of 2021. Recent decades have brought significant changes to the protein structure research field. Thanks to the genome projects and advances in structure determination methods, the number of solved protein structures has increased significantly. Protein structure research is experiencing a new renaissance, and in 2020 the number of deposited structures in the PDB database reached a new record. An assortment of many new frontiers are presented in this collection. A single Special Issue cannot give a comprehensive overview of a large field such as proteins science, but we aim to give a broad overview of current research.